Translation and validation study for the stroke self-efficacy questionnaire in stroke survivors - OĞUZ, SIDIKA (WILEY, 2018)
Background: Self-efficacy has been shown to play an important role in rehabilitation outcomes of stroke patients. Aim: This study aimed to determine the validity and reliability of a Turkish translation of the Stroke Self-Efficacy Questionnaire. Methods: This methodological study was conducted in a private acute stroke unit in Istanbul, Turkey. After obtaining the Institutional Review Board's approval and site consent, a translated version of the 13-item Likert-type scaled questions was tested for language and content validity. A pilot study with 10 patients was followed by recruitment of 130 stroke patient participants, with 50 patients retested after 3 weeks. Results: The Stroke Self-Efficacy Questionnaire-Turkish had excellent content validity index and face validity index scores. Confirmatory factor analysis findings revealed a single factor structure that offered good model suitability. Cronbach alpha was 0.93 for the scale and its subgroups. There was no statistically significant difference between the items according to test-retest scores (P > 0.05), and a reliability index was over 0.80. Conclusion: The Turkish version of the Stroke Self-Efficacy Questionnaire is a valid and reliable tool. recommended for use in clinical rehabilitation and stroke self-management/selfefficacy interventions.
Keywords: questionnaires; rehabilitation; self-efficacy; stroke; QUALITY-OF-LIFE; CONTENT VALIDITY; DEPRESSION; RELIABILITY; CONFIDENCE; RECOVERY; VERSION; FACE